Концепт „олигарх”: опыт корпусного анализа - Горбунова, Людмила (Studia Rossica Posnaniensia, 2021)
The structure, content and communicative significance of the oligarch concept are explicated using corpus analysis. The structure of the oligarch concept is asymmetric: the logical and figurative components are presented much more narrowly than the axiological one. The axiological component dominates the structure of the concept. Various assessments from the negative zone of the axiological scale are included in the axiological component of the concept. The logical components of the concept are ‘the presence of very significant financial resources’, ‘the source of finance – most often oil or other extractive industry’,‘power’, ‘participation in the actual government of the country’, ‘belonging to a certain country (more often Russia or Ukraine)’, and ‘opposition to official authorities and government’. The status of “oligarch” is associated with a small number of the same persons. All logical components are assessed negatively, disparagingly or ironically. The concept of an oligarch receives significant signs from the concept of wealth – the main part of the logical component and axiology. The article compares the axiological components of the concepts oligarch and wealth. As a result, the attitude of the “ordinary Russian people” to wealth and the oligarchs is revealed: this is envy and distrust, a rich person has extremely negative qualities and has accumulated wealth in an illegal or immoral way.